RE-ACTUALIZATION OF THE INSTITUTIONALIZATION OF MUI FATWAS IN THE INFORMATION TECHNOLOGY (IT) ERA - Dahlia Haliah Ma'u (Universitas Islam Negeri (UIN) Mataram, 2022)
Social dynamic development along with the rapid change of science and technology has aroused varied social religious problems that cannot be accommodated by sharia rule contained in Al-Qur’an and Hadith. Thus, the ijtihad of Islamic scholars is the solution to these matters. In Indonesia, a legal institution that serves as a place for Islamic scholars’ doing ijtihad to overcome such problems is known as Majelis Ulama Indonesia (MUI). It was founded on 26 July 1975 in Jakarta, and has made many fatwas which must be previously addressed in fatwa commission meeting. In other words, the fatwas must be discussed with all members of MUI. In line with the modernity of information technology, the institution may formulate fatwas through online media in which the members of MUI need not gather in a particular place to determine fatwas as they have since 1975 up to now. Therefore, this research aims to propose the usage of internet applications that may be employed by MUI in formulating fatwas as solution to present social problems.